Therapeutic Potential of Kelp Fucoidan in Rebiosis of Gut Microflora and Immune Homeostasis in Cyclophosphamide-Induced Immunosuppressed Mice - Yaqing Liu; Ruining Kang; Yanfei Zhao; Heng Zhang; Qingfeng Rong; Shaoxuan Yu; Yaoguang Chang; Zhengpeng Wei; Lanlan Zhu (Foods)
Recent studies indicate that fucoidan may play a crucial role in the metabolism and biological function of the intestinal flora. This study investigates the therapeutic potential of kelp fucoidan on the gut microbiota and immune homeostasis of cyclophosphamide-induced immunosuppressed mice. An immunosuppressive mouse model was established using cyclophosphamide, followed by administration of various kelp fucoidan doses (low-dose fucoidan: 50 mg/(kg·bw)/d, medium-dose fucoidan: 100 mg/(kg·bw)/d, and high-dose fucoidan: 150 mg/(kg·bw)/d) to the experimental groups. Changes in the gut microbiota structure were analyzed using 16S rRNA high-throughput sequencing, alongside simultaneous measurement of serum immune indicators and levels of short-chain fatty acids (SCFAs). Results indicate that kelp fucoidan significantly improved the thymus and spleen indices in immunosuppressed mice (p < 0.05) and elevated serum levels of IgM, IgG and IL-4. Post-kelp fucoidan intervention, there was significant alteration in microbiota ecosystem restructuring, such as proliferation in probiotics, including Lactobacillus and Bifidobacterium, while opportunistic pathogens, such as Enterococcus and Escherichia coli, decreased. Furthermore, the levels of acetic, propionic, and butyric acids in the colonic contents of the kelp fucoidan group significantly improved (p < 0.01). This research demonstrates that kelp fucoidan enhances immune function in immunosuppressed mice by modulating gut microbiota balance and promoting short-chain fatty acid production.